Pengaruh Digital Marketing, Influencer dan Media Sosial Terhadap Konsumen - Christian Nano Putra; Syofian; Idham Lakoni (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
This study aims to find out whether digital marketing, influencers and social media have an effect on consumers at the Kevin Sport & Florist Bengkulu Shop. The population in this study are all consumers who shop at the Kevin Sport & Florist Bengkulu Store. The sample of this research is 180 people. In this study the sampling technique used was accidental sampling technique. The method of analysis of this research is a quantitative method using multiple linear regression analysis tools, multiple correlation, determination, t test and F test which are processed using IBM SPSS 21 software. From the results of the study it can be concluded that partially, digital marketing has no effect on consumers, influencers have an effect on consumers and social media has an effect on consumers. Simultaneously, digital marketing, influencers and social media influence consumers at the Kevin Sport & Florist Bengkulu Shop